ORE FLUID GEOCHEMISTRY OF THE JINLONGSHAN CARLIN-TYPE GOLD ORE BELT IN SHAANXI PROVINCE, CHINA - Zhang J.; Chen Ya.; Zhang F.; Li Ch. (My University, 2006)
The Jinlongshan gold ore belt in southern Shaanxi Province contains a number of Carlin-type gold deposits in the Qinling collisional orogenic belt. Their fluid inclusions are of the Na+ − Cl− type. From the main metallogenic stage to later stages, the total quantity of anions and cations, temperature and deoxidation parameter (R) for fluid inclusions all gradually decreased, suggesting the gradual intensification of fluid oxidation, the reduction of metallogenic depth and the input of meteoric water and organic components. The deposits were formed during crustal uplifting and hence had similar tectonic settings to orogenic gold deposits. The CO2 contents and CO2/H2O values of the ore fluid increased from early to late stages, and the wall-rock alteration is represented by decarbonation, which is inconsistent with the characteristics of orogenic gold deposits. It is also discovered that Na+, K+, SO 4 2− , Cl− and the total amounts of anions and cations in the inclusions in quartz are higher than those in the coexisting calcite. The H, O and C isotope ratios indicate that the ore fluid was sourced from meteoric water and metamorphic devolatilisation of the sedimentary rocks that host the ores. The high background δ18O and δ13C values of wall rocks resulted in high δ18O and δ13C values of ore fluid and also high δ18O and δ13C values of hydrothermal minerals such as quartz and carbonate. The carbon in ore fluid stemmed largely from the hosting strata. The δ18O and δ13C values of Fe-calcite and the δD values of fluid inclusions are lower than those of calcite and quartz. In terms of the theory of coordination chemistry, all these differences can be ascribed to water-rock interaction in the same fluid system, instead, to the multisource of ore fluid.
Keywords: ORE FLUID; JINLONGSHAN GOLD ORE BELT; CARLIN-TYPE GOLD DEPOSIT; ISOTOPE; FLUID INCLUSION; QINLING OROGEN